The Leap of Faith The Fiscal Foundations of Successful Government in Europe and America - Steinmo, Sven H. (Oxford University Press, 2018)
This is the first book to compare the history of tax compliance in several countries (Sweden, Britain, Italy, Romania, and the United States). The book clearly elaborates the policy lessons from the five cases explored for countries who are currently trying to build successful and effective tax policies. Makes the direct connection between historical cases and current policy issues in developed and developing countries.